Design of an added plan with social responsibility - Kathya Alexandra Suesca Rozo; Andrés Felipe Santos Hernández (The Road to a Digitalized Supply Chain Management: Smart and Digital Solutions for Supply Chain Management. Proceedings of the Hamburg International Conference of Logistics (HICL), Vol. 25, 2018)
For decades and worldwide, steel has been one of the most important commodity in the development of the industry due to its multiple uses. At present, the offer of steel in Colombia is too low compared to the sector's demand. This has caused market speculation and a low added value regarding all products made with steel. In such a competitive market, the organizations involved have been developing strategies to improve their incomes, some of these are developed in the operations area, where the planning is the most important part regarding the cost reduction, minimize the rate of rotation of the personal in the operations area and increment in the effectivity of the supplies chain. Having this need and tendency created, the investigation group designed an added planning model, based on the case of an enterprise that transforms steel in cloves. Using this model in the enterprise will guarantee decrease the shortage in posterior periods and as consequence lower the costs and wastes caused by shortfalls, the costs of keeping an inventory and costs due to high lead time to market. Furthermore, the model will minimize the rate of rotation of the personal in the operations area, this will result encouraging social responsibility which contribute to the organization's productivity.
urn:nbn:de:gbv:830-882.023812; 10419/209194; https://econpapers.repec.org/RePEc:zbw:hiclpr:25
Keywords: 650; Steel transformation; Added planning; Optimization; Social responsibility